2005
DOI: 10.1074/jbc.m411999200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between LRP5 and Frat1 Mediates the Activation of the Wnt Canonical Pathway

Abstract: Low density lipoprotein receptor-related protein 5 (LRP5) has been identified as a Wnt co-receptor involved in the activation of the ␤-catenin signaling pathway. To improve our understanding of the molecular mechanisms by which LRP5 triggers the canonical Wnt signaling cascade, we have screened for potential partners of LRP5 using the yeast two-hybrid system and identified Frat1 as a protein interacting with the cytoplasmic domain of LRP5. We demonstrate here that LRP5/Frat1 interaction is involved in ␤-cateni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…We show that the expression of Msi1 is regulated in a cell-autonomous way by the Wnt pathway. Lentiviral-mediated increase in the expression of Msi1, in turn, stimulates the Wnt pathway through the induction of Frat1, a potent activator of -catenin stabilization (Hay et al, 2005;van Amerongen et al, 2005). Finally, we also show that Msi1 overexpression has the potential to induce tumor formation in a xenograft model.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…We show that the expression of Msi1 is regulated in a cell-autonomous way by the Wnt pathway. Lentiviral-mediated increase in the expression of Msi1, in turn, stimulates the Wnt pathway through the induction of Frat1, a potent activator of -catenin stabilization (Hay et al, 2005;van Amerongen et al, 2005). Finally, we also show that Msi1 overexpression has the potential to induce tumor formation in a xenograft model.…”
Section: Introductionmentioning
confidence: 62%
“…More importantly, our data also showed that Frat1 mRNA was significantly increased by Msi1 overexpression, as compared with the level in the control cells. Interestingly, Frat1 is known to be a potent activator of the canonical Wnt pathway (Hay et al, 2005). This protein is dispensable with regard to Wnt--catenin signaling, but it can enhance the accumulation of activated -catenin (van Amerongen et al, 2005).…”
Section: Overexpression Of Msi1 Cdna In Intestinal Epithelial Primarymentioning
confidence: 99%
“…We consider it unlikely that the ctail binds to itself directly: it does not form puncta on its own (Fig. 2C,D), was not found in any of the yeast two-hybrid screens with ctail baits (Hay et al, 2005;Mao et al, 2001b;Mi et al, 2006;Tolwinski et al, 2003), and is predicted to be intrinsically disordered (Piao et al, 2008). Therefore, in all probability, the stability of the DIX>ctail puncta is conferred by ctail-binding factor(s) that function to stabilize ('cross-link') the labile DIX-mediated self-interaction, e.g.…”
Section: Stability Elements Outside the Pppspxs Motifs Enable The Lrpmentioning
confidence: 99%
“…In this complex, β-catenin is phosphorylated and degraded by the ubiquitin-proteasome pathway. Wnt binding recruits Axin1 to the receptor complex, where it binds the cytoplasmic domain of LRP5 (Cong et al, 2004;Hay et al, 2005;Mao et al, 2001). Axin1 is a central component of the canonical Wnt pathway and acts as a scaffold for the protein complex involved in β-catenin degradation.…”
Section: Introductionmentioning
confidence: 99%